LAW ENFORCEMENT CONCERNING THE CRIME OF MONEY LAUNDERING BASED ON PANCASILA - Muhammad Ridwan Lubis (Unissula, 2022)
The purpose of this research is to find out about law enforcement regarding the crime of money laundering in Indonesia based on Pancasila, and what are the obstacles faced. This study uses a normative juridical approach, the results of the study state that the crime of money laundering is legally regulated in Law no. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. In Article 4 of Law no. 8 of 2010, also imposed on those who enjoy the proceeds of the crime of money laundering which is imposed on any person who hides or disguises the origin, source of location, designation, transfer of rights, or actual ownership of Assets which he knows or reasonably suspects is proceeds of a crime. In the crime of money laundering, there are at least two major problems in carrying out investigations and investigations faced by a country.